Number 19 (July 1989) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1989)
(July 1989) - Atlas of Fishes of the Upper Tombigbee River Drainage, Alabama-Mississippi. By H.T. Boschung, 104 pp.
Keywords: fishes; tombigbee; river; alabama; mississippi